2021
DOI: 10.3390/app112311160
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Modern Reciprocal Endodontic Systems and Fatigue Failure Testing in Simulated Clinical Conditions

Abstract: Instrument fracture ranks among the most crucial complications during the endodontic treatment of a tooth. In order to better understand the practical limits of the instrument, the relation between the cyclic fatigue resistance and physical properties such as hardness, modulus of elasticity, creep and surface roughness were explored. Cyclic fatigue testing in an artificial root canal at intracanal temperature, nanoindentation and 3D microscopy were used for evaluation of four commonly used thermomechanically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…Due to the fact that the examined files employ the reciprocating-movement technique, the present investigation did not investigate the torque exerted. Attempts were undertaken in the current investigation to ensure comparability of the experimental groups despite variances in the morphology of natural teeth 24 . Straight canals were included to remove the effect of the inclination of force vectors, which could impair the accuracy of the measurements, and constricted canals were chosen for this study and confirmed to give extra challenges for the canal shaping (39).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that the examined files employ the reciprocating-movement technique, the present investigation did not investigate the torque exerted. Attempts were undertaken in the current investigation to ensure comparability of the experimental groups despite variances in the morphology of natural teeth 24 . Straight canals were included to remove the effect of the inclination of force vectors, which could impair the accuracy of the measurements, and constricted canals were chosen for this study and confirmed to give extra challenges for the canal shaping (39).…”
Section: Discussionmentioning
confidence: 99%